Recording Interest Income in the Balance of Payments - Harper, Peter (IMF Working Papers; Working Paper ;, 1995)
In the balance of payments, as well as the national accounts, income refers to the use of factors of production. Accordingly, income should be recorded in the balance of payments during the period or periods in which the economic benefits arising from the use of a factor of production are enjoyed by the user-that is, on an accrual basis. This paper discusses: (1) the theoretical implications of using the accrual basis for recording interest income, including the nature of entries necessary to offset income accrued but not paid and the calculation of accrued interest; and (2) the practical aspects of measuring interest on this basis.